2016
DOI: 10.1109/tdei.2016.005886
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced breakdown performance of Anatase and Rutile titania based nano-oils

Abstract: Nano-oils synthesized by dispersing dielectric nanostructures counter common intuition as such nano-oils possess substantially higher positive dielectric breakdown voltage with reduced streamer velocities than the base oils. Nano-oils comprising stable and dilute homogeneous dispersions of two forms of titanium (IV) oxide (TiO 2 ) nanoparticles (Anatase and Rutile) have been experimentally examined and observed to exhibit highly enhanced dielectric breakdown strength compared to conventional transformer oils. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The electrons propagating with high velocity under high‐voltages interacts with the water molecules and releases the free electrons due to its inherent polar nature. So the raise in free‐electron density offers the conducting path in TTNF and increases its electrical conductivity, which leads to the reduction of BD voltages [37].…”
Section: Results Discussion With Relevant Theoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrons propagating with high velocity under high‐voltages interacts with the water molecules and releases the free electrons due to its inherent polar nature. So the raise in free‐electron density offers the conducting path in TTNF and increases its electrical conductivity, which leads to the reduction of BD voltages [37].…”
Section: Results Discussion With Relevant Theoriesmentioning
confidence: 99%
“…There exist certain methods to develop moisture in the oil samples, and to feed the saturated nitrogen into the test cell equipped with the gas line is one among that [58]. Katiyar et al [37] developed moisture in anatase and rutile TiO 2 nano oils by leaving it idle in the atmosphere for different time periods, to study its humidity ageing. Vahidi et al [59] studied the humidity ageing of MO for different levels of relative humidity (RH) in the chamber and clearly verified the rapid water absorption occurs at the higher intensity of RH.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Katiyar et al [61] have the opinion that the existence of a surfactant has an insignificant effect on the viscosity, thermal conductivity, and breakdown voltages. Furthermore, Xuan et al reported that the sodium dodecyl benzoic sulphate (SDBS) surfactant remarkably exerts a negative effect on the impinging heat transfer performance and suspension of nanofluids.…”
Section: Synthesisation Of Nanofluidsmentioning
confidence: 99%
“…The performance of the insulating oils can be improved by suspending nanoparticles into the transformer oils such as magnetite and semiconductor particles. Also, the improvement is attained by enhancing the thermal characteristics of the insulating oils [2][3][4][5][6][7][8][9][10]. The induced and polarised charges generated on the surface of the nanoparticles play an important role in capturing electrons and then enhancing the dielectric strength of the insulating oils [3].…”
Section: Introductionmentioning
confidence: 99%